Characterization of the CD200 receptor family in mice and humans and their interactions with CD200. - Wright, G; Cherwinski, H; Foster-Cuevas, M; Brooke, G; Puklavec, M; Bigler, M; Song, Y; Jenmalm, M; Gorman, D; McClanahan, T; Liu, MR; Brown, M; et al. (2003)
CD200 (OX2) is a broadly distributed cell surface glycoprotein that interacts with a structurally related receptor (CD200R) expressed on rodent myeloid cells and is involved in regulation of macrophage function. We report the first characterization of human CD200R (hCD200R) and define its binding characteristics to hCD200. We also report the identification of a closely related gene to hCD200R, designated hCD200RLa, and four mouse CD200R-related genes (termed mCD200RLa-d). CD200, CD200R, and CD200R-related genes were closely linked in humans and mice, suggesting that these genes arose by gene duplication. The distributions of the receptor genes were determined by quantitative RT-PCR, and protein expression was confirmed by a set of novel mAbs. The distribution of mouse and human CD200R was similar, with strongest labeling of macrophages and neutrophils, but also other leukocytes, including monocytes, mast cells, and T lymphocytes. Two mCD200 receptor-like family members, designated mCD200RLa and mCD200RLb, were shown to pair with the activatory adaptor protein, DAP12, suggesting that these receptors would transmit strong activating signals in contrast to the apparent inhibitory signal delivered by triggering the CD200R. Despite substantial sequence homology with mCD200R, mCD200RLa and mCD200RLb did not bind mCD200, and presently have unknown ligands. The CD200 receptor gene family resembles the signal regulatory proteins and killer Ig-related receptors in having receptor family members with potential activatory and inhibitory functions that may play important roles in immune regulation and balance. Because manipulation of the CD200-CD200R interaction affects the outcome of rodent disease models, targeting of this pathway may have therapeutic utility.